Changes in Quality of Alimentation, Anthropometric Measurements, Emotional and Appetite Status of Bariatric Surgery Patients: A Retrospective Cohort Study - Özenir, Çiler; Erdem, Nihal Zekiye; Kaçar, Mihrican; Öncel, Sevgi Yurt (International Journal of Statistics in Medical Research, 2024)
Introduction: Laparoscopic adjustable gastric band (LAGB) operation is one of the bariatric surgery methods used to treat extreme obesity. Objective: This study aimed to evaluate the changes in food tolerance, quality of alimentation, anthropometric measurements, and emotional and appetite status following LAGB. Materials and methods: A retrospective cohort study was conducted with 98 patients, 1 year had passed since LAGB. In this study, no sample selection method was used; all patients who met the inclusion criteria and volunteered participated. The questionnaire form included questions to determine the patients’ demographic information, anthropometric measurements, changing food consumption, pre- and post-operative meal consumption, appetite and emotional status. Quality of Alimentation (QA) reflects patients’ post-operative dietary satisfaction and tolerance. The QA Form was used to evaluate post-operative food tolerance. Results: The average age was 38.61±9.82 years, and the mean QA score was 15.59±4.81. The patients lost an average of 30.80±17.76 kg of body weight from pre-operative to post-operative 1st year, and the percentage of patients’ excessive body weight loss was found to be 54.37±26.42. It was determined that the foods that were most difficult to consume after the operation were red meat, white meat, bread, rice, pasta, and salad, respectively. Conclusions: This study uniquely evaluates food tolerance using the QA Form, offering insights into post-operative dietary challenges. LAGB effectively reduces appetite, promotes weight loss, and has a positive impact on patients’ emotional health.